2013
DOI: 10.1155/2013/951392
|View full text |Cite
|
Sign up to set email alerts
|

C‐Glycosidic Genistein Conjugates and Their Antiproliferative Activity

Abstract: This paper presents our attempt to investigate scopes and the limitations of olefin cross-metathesis (CM) reaction in the synthesis of complex C-glycosides of genistein and evaluation of their antiproliferative activities. Novel genistein glycoconjugates were synthesized with the utility of CM reaction initiated by first and second generation of Grubbs catalysts. The relative reactivity of utilized olefins, based on categories proposed by Grubbs, was estimated.In vitroexperiments in cancer cell lines showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…antioxidant potential, whereas O-glycosylation reduces flavonoid bioactivity and (iii) although the structure of aglycone is responsible for the bioactivity, the bioactivity of flavonoid C-glycosides may be different from that of the aglycones. [1][2][3][4][5][6] Recently, a systematic increase in the number of papers devoted to the flavonoid C-glycosides has been noted, in particular those devoted to the one specific flavonoid C-glycoside known to show interesting biological activities. For example vitexin or isovitexin show a number pharmacological properties, however, the most promising seems to be their anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…antioxidant potential, whereas O-glycosylation reduces flavonoid bioactivity and (iii) although the structure of aglycone is responsible for the bioactivity, the bioactivity of flavonoid C-glycosides may be different from that of the aglycones. [1][2][3][4][5][6] Recently, a systematic increase in the number of papers devoted to the flavonoid C-glycosides has been noted, in particular those devoted to the one specific flavonoid C-glycoside known to show interesting biological activities. For example vitexin or isovitexin show a number pharmacological properties, however, the most promising seems to be their anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively simple structure of the genistein molecule and the many possibilities of its derivatization offer ample space for obtaining derivatives with improved activity or affecting new molecular targets [24]. In the previous work, we described glycoconjugates of genistein inhibiting cancer cell proliferation more efficiently than genistein [25,26,27,28,29]. The aim of this work was to evaluate EGFR tyrosine kinase inhibition by selected genistein derivatives and to explore the biological effects of these compounds used in combination with ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that genistein glycoconjugates (Fig. 10D) exhibit anti-proliferative potential [313, 317, 318] and even induce cell cycle arrest [319, 320]. Interestingly, some of these analogs also inhibited microtubule assembly [318, 319, 321].…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%